(untitled) (The Agriculturists, 2014)
A study was conducted to evaluate the effect of yeast Saccharomyces cerevisiae and algae Chlorella vulgaris on the production of rotifer Brachionus calyciflorus. The Brachionus calyciflorus were cultured using four different types of diets: fresh Chlorella vulgaris (T1), yeast with fresh Chlorella vulgaris (T2), powder Chlorella vulgaris with fresh Chlorella vulgaris (T3) and yeast with powder Chlorella vulgaris (T4). We compared these diets to find out their potentiality on the population growth of Brachionus calyciflorus. The rotifers were cultured under natural environmental condition with continuous artificial aeration. Initial density of Brachionus calyciflorus were 8 individuals ml-1 (ind. ml-1). Water temperature and pH were measured during the culture period. Among the four different diets the fresh Chlorella vulgaris (T1) and its yeast combination (T2) gave satisfactory production of rotifer 73±9 and 67±8 ind. ml-1, respectively. However, processing of fresh Chlorella vulgaris to produce powder form declined the production ability of rotifer. The diet sample T3 and T4 containing powdered Chlorella vulgaris produced 48±9 and 25±6 ind. ml-1, respectively. So, the diet in combination of yeast and fresh Chlorella is suggested for the sustainable production of the rotifer Brachionus calyciflorus. DOI: http://dx.doi.org/10.3329/agric.v12i1.19484 The Agriculturists 2014; 12(1) 1-9